Exploring students’ conceptual understanding of parallelograms based on Geogebra - Delaviz, M.; Leong, K.E. (2013)
This study used a mixed mode approach and aimed to explore students’ conceptual understanding in geometry using GeoGebra. The focus of this study was on the concept of parallelograms. This study was conducted in an Iranian governmental boys’ school using ten grade two lower secondary school students as participants. These students were randomly divided into two groups. The first group underwent the lesson using the GeoGebra whereas the other group was taught using the traditional approach. This research findings focused more on the qualitative section and less on the quantitative section in which detailed observation were executed as well as the mean scores and standard deviation of both groups were compared. Non-equivalent pre-test and post- test were administered respectively to evaluate students pre-requisite knowledge and conceptual understanding of the concepts of parallelograms. The findings of this research will be useful to mathematics’ teachers in planning for their geometrical activities.